Synthesis and characterization of Y-doped AlZn2O4 spinels - Kebiroglu, Hanifi; Hssaın, Ala; Mahmood, Bahroz Kareem; Kaygili, Omer (Niyazi BULUT, 2021)
Zinc aluminum oxide (ZnAl2O4) type spinel samples doped with Y at various amounts of 0, 5, 10, and 15 at.% were produced and characterized for this study. Both X-ray diffraction (XRD) and Fourier transform infrared (FTIR) analyses confirmed the formation of the ZnAl2O4 phase for all the samples. For the spinels doped with Y at the amounts of 10 and 15 at.%, the formation of the secondary phase of Y2O3 was detected. The average crystallite size, lattice constant, unit cell volume, and crystallinity were affected by Y content, as well as the morphology.
Keywords: Metrology; Applied and Industrial Physics; Metroloji; Uygulamalı ve Endüstriyel Fizik